Socio-Economic Security: Modern Approach to Ensuring the Socio-Economic Development of the Region (Economics and region, 2019)
The advantages of the program-targeted approach in ensuring region economic security are considered. It is noted that regional development programs can be a real tool for accelerating the region’s economy reforming. Directions of increasing the effectiveness of program-target program method as a tool for regional economy regulating and to ensure regional economic security are defined. The necessity of region’s social and economic security ensuring as an integral part of the socio-economic development strategy of the region is substantiated. A list of the main provisions of the regional strategic program for ensuring the socio-economic security of the region is proposed. The main objectives of the program ensuring the region’s socio-economic security are defined. It is proved that the regional socio-economic security program determines the structural restructuring directions of the economic system of the region, taking into account local potential and features of the territory and is made on the basis of economic forecasts for the region development. The conditions for the program effectiveness are stated. The subjects of the regional economic security program implementation and their responsibilities are specified. The sources of state financial support the region’s strategic development program and criteria’s of the regional governance effectiveness are defined.
Keywords: socio-economic security; region’s social and economic security; threats; program-targeted approach; socio-economic development of the region